Metastatic tuberculous chest wall and massive psoas abscesses in an immunocompetent patient - Mansoor C Abdulla (International Journal of Mycobacteriology, 2020)
Extrapulmonary tuberculosis (TB) is rare in immunocompetent healthy adults. TB of the chest wall accounts for 1%–5% of all cases of musculoskeletal TB. Psoas abscess can be either primary or secondary to diseases like Pott's spine. We describe a patient with massive lower chest wall abscess extending to abdominal muscles and an asymptomatic large psoas abscess detected on imaging due to spine TB which responded well to antitubercular therapy and drainage without surgical measures. The concomitant presence of a massive chest wall abscess and psoas abscess due to TB in an immunocompetent patient was not reported previously.